2020
DOI: 10.1097/md.0000000000019925
|View full text |Cite
|
Sign up to set email alerts
|

The computation of case fatality rate for novel coronavirus (COVID-19) based on Bayes theorem

Abstract: Background: When a new disease such starts to spread, the commonly asked questions are how deadly is it? and how many people are likely to die of this outbreak? The World Health Organization (WHO) announced in a press conference on January 29, 2020 that the death rate of COVID-19 was 2% on the case fatality rate (CFR). It was underestimated assuming no lag days from symptom onset to deaths while many CFR formulas have been proposed, the estimation on Bays theorem is worthy of interpretation. Hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…The results showed that Hong Kong, Shanghai, and Hubei are the top three cities most affected by COVID-19, with IPcase indices of 1744, 723, and 698; respectively, quite different from the results in IP or CNIC ( Figure 3 and Figure 4 ) alone in analyses. Using the single CNIC [ 2 , 3 ] to compare the negative impact of COVID-19 is problematic and unreasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that Hong Kong, Shanghai, and Hubei are the top three cities most affected by COVID-19, with IPcase indices of 1744, 723, and 698; respectively, quite different from the results in IP or CNIC ( Figure 3 and Figure 4 ) alone in analyses. Using the single CNIC [ 2 , 3 ] to compare the negative impact of COVID-19 is problematic and unreasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Which countries/regions were severely affected by COVID-19 is one of the most frequently asked questions. Using the number of reported cases is common, but not fair [ 2 , 3 ]. Several pandemic-prevention measures such as lockdowns, quarantines, mask-wearing, social distancing, contact reduction, and triggering bold policies on containment and mitigation have been implemented in several countries to flatten the curve of COVID-19 [ 4 ] cases and to decrease the strain on the public and health care systems in their areas as much as possible.…”
Section: Introductionmentioning
confidence: 99%
“…To calculate the adjusted CFR, we used the cumulative number of cases reported X days ago where X denotes the median number of days from diagnosis to death. 4 We calculated the median days from diagnosis to death by conducting survival analysis using the Kaplan-Meier estimate. 5 The cases which were reported as brought dead or dead at residence were not taken into consideration for this analysis.…”
Section: Case Fatality Ratesmentioning
confidence: 99%
“…CFR predominantly depends upon the number of cases who are diagnosed and labelled as 'cases', which in turn depends upon the testing rate, reporting rate, etc. 9,10 If a greater number of tests is performed, the denominator (used to calculate CFR) will keep increasing, and for a disease like COVID-19, with the number of asymptomatic/mildly symptomatic cases being high, it could capture many such asymptomatic/mildly symptomatic cases, and this would further lower the CFR. Moreover, the robustness of the diagnostic test also plays some role here in terms of false-positive rate, falsenegative rate, etc.…”
Section: Case Fatality Ratementioning
confidence: 99%